Implementation of a Nutrition-Oriented Clinical Decision Support System (CDSS) for Weight Loss during the COVID-19 Epidemic in a Hospital Outpatient Clinic: A 3-Month Controlled Intervention Study - Paraskevi Detopoulou; Panos Papandreou; Lida Papadopoulou; Maria Skouroliakou (Applied Sciences, 2023)
Clinical Decision Support Systems (CDSSs) facilitate evidence-based clinical decision making for health professionals. Few studies have applied such systems enabling distance monitoring in the COVID-19 epidemic, especially in a hospital setting. The purpose of the present work was to assess the clinical efficacy of CDSS-assisted dietary services at a general hospital for patients intending to lose weight during the COVID-19 pandemic. Thirty-nine patients (28 men, 71.8%) comprised the intervention group and 21 patients (four men, 16%) of the control group. After a 3-month CDSS intervention, reductions in both body weight (mean ± standard deviation (SD): 95.5 ± 21.8 vs. 90.6 ± 19.9 kg, p < 0.001) and body mass index (BMI) (median, interquartile range (IQR): 35.2, 28.4–37.5 vs. 33.2, 27.4–35.4 kg/m2, p < 0.001) were observed. Beneficial effects were also recorded for total body fat (44.9 ± 11.3 vs. 41.9 ± 10.5%, p < 0.001), glycated hemoglobin (5.26 ± 0.55 vs. 4.97 ± 0.41%, p = 0.017) (mean ± SD) and triglycerides (137, 115–152 vs. 130, 108–160 mg/dL, p = 0.005) (medians, IQR). Lean tissue was borderline decreased (25.4, 21.7–29.1 vs. 24.6, 21.8–27.9 kg, p = 0.050). No changes were documented in the control group. In multivariate linear regression models, serum triglycerides were inversely associated with % absolute weight loss (B = −0.018, standard error (SE) = 0.009, p = 0.050) in the CDSS intervention group. In women, a principal component analysis-derived pattern characterized by high BMI/lean tissue was positively related to % absolute weight loss (B = 20.415, SE = 0.717, p = 0.028). In conclusion, a short-term CDSS-facilitated intervention beneficially affected weight loss and other cardiovascular risk factors.